Esl Teaching Strategies And Techniques To Enhance Speaking In The Efl Adolescents And Young Adult Population. (2018)
It is important to take into account that English is one of the most important universal languages. In our Latin American culture, English has become crucial in schools, Universities, work places and some other institutions. It is also important to note that this language is learned and taught worldwide; therefore, the importance on learning how to teach it properly (Verghese, 1987). Additionally, in Colombia and around the world, research is mostly about how to teach writing and reading to children and adolescents. Many different kinds of strategies and techniques are found in theses, articles, and books, but not many of them are focused on students’ speaking ability